KUALITAS TELUR AYAM RAS PETELUR YANG DIBERI SUPLEMENTASI TEPUNG DAUN KELOR (Moringa oleifera) DALAM RANSUM - Supranoto Supranoto (Fakultas Peternakan Universitas Wijaya Kusuma Purwokerto, 2020)
This study aimed to examine the effect of dietary supplementation of moringa leaf meal (Moringa oleifera) on the egg quality of commercial laying hens. A total of 80 ISA Brown laying hens aged ±40 weeks were used in an experiment arranged in a completely randomized design (CRD) consisting of 4 treatments and 5 replications, with 4 hens per replication. The treatments were the inclusion of moringa leaf meal in the diet at P0 (0%), P1 (2%), P2 (4%), and P3 (6%). The observed variables were egg weight, shell thickness, Haugh Unit (HU), yolk index, yolk colour score, and yolk cholesterol content. Data were analysed using analysis of variance followed by the Least Significant Difference (LSD) test. The results showed that moringa leaf meal supplementation significantly affected (P